Heavily n‐type ZnO: A plasmonic material at telecommunication wavelengths. Issue 7 (7th April 2014) - Kalusniak, Sascha; Sadofev, Sergey; Schäfer, Peter; Henneberger, Fritz
Abstract: Doping of ZnO by Ga allows for generation of free electrons up to concentrations of about 1021 cm –3 without significant deterioration of the crystal structure. In this way, a metallic dielectric function is formed with a negative real part tuneable from the mid infrared up to telecommunication wavelengths. The losses are about one order of magnitude lower than in traditional metals. We demonstrate surface plasmon polaritons with dispersion relations that can be engineered in a unique way by utilizing epitaxial multi‐layer structures of different doping level. In contrast to the standard air/metal excitations, the surface‐plasmon‐polariton frequency approaches a finite value in the zero‐wavevector limit at metal/metaltype interfaces. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)